Body Cameras and Adjudication: Views of Prosecutors and Public Defenders - Robertson, O. Nicholas (Criminal justice review, 2024)
The jury serves as an important reference point for criminal case processing, despite the fact that the majority of cases are disposed of by pleas or dismissals. This research examines the downstream impact of BWC footage on the adjudication process with a particular emphasis on the management of uncertainty. Research involved interviews with prosecutors and defense attorneys in urban counties in California, New York, and Texas. The results indicate that both defense and prosecution anticipate BWC changing approaches to cases and how cases may be negotiated to an outcome. They also report that jurors expect BWC footage, and that it functions as a means to establish case facts and the credibility of police, the defendant and witnesses. Policy implications regarding the introduction of BWC and future directions for research are discussed.